Kunitz trypsin inhibitor polymorphism in the Korean wild soybean (Glycine soja Sieb. & Zucc.). Issue 3 (3rd April 2013) - Krishnamurthy, Panneerselvam; Singh, Ram J.; Tsukamoto, Chigen; Park, Jong Hyun; Lee, Jeong Dong; Chung, Gyuhwa; Link, W.
Abstract Kunitz trypsin inhibitor (KTi) in 1368 accessions of wild soybean (Glycine soja Sieb. & Zucc.), collected from three regions of Korea, was examined for allelic diversity and geographical distribution. Five electrophoretically distinguishable KTi forms were detected: three were common (Tia, Tib and Tia/Tib) and two were previously unreported (Tibi7‐1 and Tibi5). The Tia allele was predominant (93.49%). Alleles Tib, Tibi7‐1 and Tibi5 were detected with the frequencies of 3.47, 0.55 and 0.11%, respectively. The heterozygous form (Tia/Tib) was detected with the frequency of 2.26%. The nucleotide sequence of Tibi7‐1 was identical to that of the Tib‐derived variant allele Tif, with the exception of three nucleotides: A→G at position +244, A→C at position +286 and G→C at position +601. The latter two were similar to Tia, suggesting that Tibi7‐1 is an intermediate allele between Tia and Tib. The gene for Tibi5 showed 100% similarity with the Japanese intermediate allele Tibi5. This study demonstrates that Korean wild soybeans are remarkably rich source of new KTi alleles not reported before.